Topical mitomycin C chemotherapy in the management of ocular surface neoplasia: a 10-year review of treatment outcomes and complications. Issue 10 (8th June 2010) - Russell, H C; Chadha, V; Lockington, D; Kemp, E G
Abstract : Introduction: The use of topical mitomycin C (MMC) has gained popularity in the management of ocular surface neoplasia. The aim of this study is to determine outcomes and complications following such treatment. Methods: This study is a retrospective review of patients treated with topical MMC for ocular surface neoplasia, including primary acquired melanosis (PAM), melanoma, corneal–conjunctival intraepithelial neoplasia (CCIN), squamous cell carcinoma (SCC) and sebaceous gland carcinoma (SGC). Data regarding diagnosis, short- and long-term outcomes, and short- and long-term complications, were recorded. Results: 58 patients were identified, with a mean age of 63 years and mean follow-up of 36 months. 21 received MMC as primary therapy and 37 as surgical adjuvant. The regimen was 0.04% MMC four times a day for 3 weeks on, 3 weeks off, 3 weeks on, with topical steroid and lubricants throughout. Initial clinical response was either partial or complete in 93%. Overall, 26% developed recurrent disease at a mean of 13 months post treatment. Recurrence rates by pathology were 20% PAM, 25% melanoma, 0% CCIN, 67% SCC and 57% SGC. Short-term complications occurred in 52%, but only 7% required treatment cessation. Long-term complications such as persisting keratoconjunctivitis, epiphora and corneal problems, occurred in 31%. Conclusion: The results confirm the effectiveness of topical MMC chemotherapy in the management of ocular surface neoplasia. Self-limiting short-term complications were common; however, limbal stem cell deficiency appears to be a significant long-term complication of treatment, occurring in 12%.